Suppression in haemolytic activities and specific antibody response of sera of the Indian major carps treated with malathion - Dash, Kalpana; Pandey, A K; Ayyappan, S (Indian Journal of Fisheries, 2011)
The present study describes the natural immune reaction of sera of the Indian major carps, Catla catla, Laheo rohita and Cirrhinus mrigala, with special reference to complement activation in normal as well as malathion-treated groups. Activation of complement system of these fishes was found to be mainly through the alternative pathway because level of the classical pathway (CHj^) -mediated killing of fishes was very low in all the groups (range 2-4 units/ml). Furthermore, the alternative pathway activation of fish sera (APCHg(,) is quite higher (30-40 units/ml) in all the groups of major carps indicating that complement-mediated protection was operated mainly through alternative pathway in these fishes while in higher vertebrates, the major pathway of complement activation is through classical components. Exposure of the Indian major carps to the two doses (0.25 and 3.00 ppm) of malathion significantly suppressed their natural immunity through complement cascade. Further, malathion treatment also reduces the specific antibody titre against soluble antigen (bovine serum albumin, BSA) whereas it has no effect on the natural haemagglutinin titre of these fish sera against rabbit erythroc3rtes (RaRBCs).